Viewing Room. - Gorman, Jacquelin (Flannery O'Connor Award for Short Fiction., 2013)
In The Viewing Room, two hospital chaplains console the living during the moments when they look upon their beloved dead for one last time in a large urban hospital in Los Angeles. But this room is also a character, linking stories together and bearing witness in chilling testimony of grief and wisdom. Henrietta and Maurice, the chaplains, are ministers who have lost their faith due to devastating personal tragedy. Still, they regain their hold on their own lives through their work, one death at a time. Jacquelin Gorman lays bare nine parallel worlds of suffering in stories of unflinching det.